2021
DOI: 10.1073/pnas.2014876118
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ca2+signaling, mild primary aldosteronism, and hypertension in a familial hyperaldosteronism mouse model (Cacna1hM1560V/+)

Abstract: Gain-of-function mutations in the CACNA1H gene (encoding the T-type calcium channel CaV3.2) cause autosomal-dominant familial hyperaldosteronism type IV (FH-IV) and early-onset hypertension in humans. We used CRISPR/Cas9 to generate Cacna1hM1560V/+ knockin mice as a model of the most common FH-IV mutation, along with corresponding knockout mice (Cacna1h−/−). Adrenal morphology of both Cacna1hM1560V/+ and Cacna1h−/− mice was normal. Cacna1hM1560V/+ mice had elevated aldosterone:renin ratios (a screening paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Adrenals from these animals have elevated baseline and peak intracellular Ca 2+ levels. 89 Last, a transgenic mouse with adrenocortical expression of a Gq-coupled designer receptor develops disorganization of adrenal zonation and hyperaldosteronism, 90 as in GNAQ mutations in APAs. Additional models with mutations in KCNK3 and KCNK9 potassium channels or cryptochrome genes have been reviewed elsewhere.…”
Section: Schollmentioning
confidence: 99%
See 1 more Smart Citation
“…Adrenals from these animals have elevated baseline and peak intracellular Ca 2+ levels. 89 Last, a transgenic mouse with adrenocortical expression of a Gq-coupled designer receptor develops disorganization of adrenal zonation and hyperaldosteronism, 90 as in GNAQ mutations in APAs. Additional models with mutations in KCNK3 and KCNK9 potassium channels or cryptochrome genes have been reviewed elsewhere.…”
Section: Schollmentioning
confidence: 99%
“…Therapeutic use of calcium channel blockers in PA was considered long before the discovery of calcium channel mutations 99 but approved compounds target vascular calcium channels, and their antihypertensive effect is mostly aldosterone-independent. 5 Normal aldosterone values in Cacna1h knockout mice 89,100 and the phenotype of Cacna1d knockout mice (deafness and sinoatrial node dysfunction with bradycardia and arrhythmia) 101 argue against these channels as therapeutic targets.…”
Section: Diagnostic and Therapeutic Advances Based On Genetic Discove...mentioning
confidence: 99%
“…As a main member of the T-type calcium channel, Cav3.2 channel has been reported to widely present in tissues throughout the body, including heart, brain, liver, lung, kidney and skin [12,29] . Numerous studies suggested that Cav3.2 channel play a crucial part in the development of various diseases, including myocardial infarction [13] , hypertension [14] , obesity [15] and diabetic neuropathy [16] . In addition, Cav3.2 inhibitors mibefradil and NNC 55-0396 were proven to improve hyperglycemia and hyperlipidemia in db/db mice [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Cav3.2 channel is an important member of T-type calcium channel and involved in many cellular processes with different cell activities by regulating calcium in ux, including proliferation, migration, differentiation and apoptosis [11,12] . Numerous studies suggested that Cav3.2 channel play a crucial part in the development of various diseases, including myocardial infarction [13] , hypertension [14] , obesity [15] and diabetic neuropathy [16] . However, little is known on the function of Cav3.2 channel in the progression of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, several aldosterone-associated hypertensive models generated by ion channel gain-of-function (GOF, eg, ClC-2 Clchannels [Clcn2 R180Q/+ , Clcn2 op/op ], 19,21 Ca v 3.2 calcium channels [Cacna1h M1560V/+ ] 28 ) or loss-of-function (LOF, eg, TWIK-related acid-sensitive potassium [TASK] channels [Kcnk3, Kcnk9, alone and together] 16,[29][30][31][32] ) replicate many of the defining features of human PA. Collectively, these mouse models indicate that genetically altered cells, including Cyp11b2-positive cells, can produce mild to severe RAS-independent hyperaldosteronism in vivo.…”
mentioning
confidence: 99%